Plant defence and stress acclimation : regulation by protein phosphatase 2A - Rahikainen, Moona (fi=Turun yliopisto|en=University of Turku|, 2018)
Environmental alterations challenge the plant growth and reproduction in nature and in crop fields. Plants harbour acclimatory and defensive mechanisms that become activated under unfavourable conditions to ensure the plant survival. Recognition of stress factors triggers signalling cascades in plant cell that activate changes in gene expression, induce hormonal signals and modulate plant metabolism via posttranslational modification of enzymes. Reversible protein phosphorylation, carried out by counteracting pairs of protein kinases and phosphatases, presents a major mechanism in signal transduction as well as in the control of metabolic enzymes in plant defence and stress acclimation. Protein phosphatase 2A (PP2A) is a trimeric phosphatase composed of a scaffold subunit A, catalytic subunit C and regulatory subunit B, all of which are encoded by multiple genes in the model plant Arabidopsis thaliana. PP2A regulatory subunit B’γ (PP2A-B’γ) has been previously identified as a negative regulator of salicylic acid associated defence and cell death in Arabidopsis leaves. In this PhD thesis, PP2A-B’γ target proteins and its role in regulation of plant acclimation and metabolism were further studied. PP2A-B’γ and its closest homologue PP2A-B’ζ were found to modulate the plant growth and stress acclimation under normal growth conditions and under severe abiotic stress. Moreover, PP2A-B’γ was shown to regulate enzymes in plant primary and secondary metabolism. PP2A-B’γ interacted with ACONITASE 3 (ACO3) and controlled its phosphorylation. ACO3 phosphorylation was further connected to accumulation of ACO3 protein. Both PP2A-B’γ and ACO3 abundance were discovered to affect the accumulation of mitochondrial alternative oxidase at post-translational level thus contributing to the control of cell redox balance. In addition to modulation of primary metabolism, PP2A-B’γ was found to influence the formation of 4-methoxyindole- 3-yl-methly glucosinolate (4MO-I3M GSL), a defence compound with antimicrobial activities. Moreover, PP2A-B’γ interacted with activated methyl cycle (AMC) enzymes linked to production of 4MO-I3M GSL. PP2A-B’γ regulated the protein complex formation of AMC enzymes exerting its control over the cell methylation capacity. These findings provide new information of plant acclimation under abiotic stress and regulation of stress associated adjustments in plant metabolism. Detailed knowledge of plant acclimatory and defensive mechanisms and stress induced adjustments in plant metabolism is valuable in the development of more tolerant and nutritious crops.

Vaihtelevat ympäristöolot vaikuttavat kasvien kasvuun ja lisääntymiseen sekä luonnossa että viljelmillä. Kasveilla onkin puolustus- ja sopeutumismekanismeja, jotka käynnistyvät epäsuotuisissa oloissa ja auttavat kasvia selviytymään. Stressitekijöiden havaitseminen aktivoi kasvisolussa viestejä, jotka aikaansaavat muutoksia geenien ilmenemisessä, käynnistävät hormonaalisia signaaleja ja säätelevät kasvin aineenvaihduntaa translaation jälkeisen säätelyn avulla. Vastavaikuttavien kinaasifosfataasiparien katalysoima palautuva proteiinifosforylaatio on tärkeä sekä viestinvälitystä ajava että aineenvaihdunnan entsyymejä ohjaava mekanismi kasvin puolustuksessa ja sopeutumisessa ympäristönmuutoksiin. Proteiinifosfataasi 2A (PP2A) on trimeerinen fosfataasi, joka koostuu rakennealayksiköstä A, katalyyttisestä alayksiköstä C ja säätelyalayksiköstä B. Jokaista alayksikköä koodaa usea geeni mallikasvi lituruohon (Arabidopsis thaliana) genomissa. PP2A:n säätelyalayksikön B’γ (PP2A-B’γ) on aiemmin havaittu estävän salisyylihaposta riippuvaisia puolustusvasteita ja solukuolemaa lituruoholla. Tässä väitöskirjassa on tutkittu tarkemmin PP2A-B’γ:n kohdeproteiineja ja merkitystä kasvin stressisopeutumisessa ja aineenvaihdunnan säätelyssä. PP2A-B’γ:n ja tämän homologin PP2A-B’ζ:n osoitettiin ohjaavan kasvin kasvua ja stressisopeutumista normaaleissa kasvuolosuhteissa ja vakavan abioottisen ympäristöstressin aikana. Lisäksi PP2A-B’γ:n havaittiin säätelevän entsyymejä sekä kasvin perusaineenvaihdunnassa että puolustusaineenvaihdunnassa. PP2A-B’γ:n osoitettiin vuorovaikuttavan akonitaasin ACO3 kanssa ja säätelevän tämän fosforylaatiota. Lisäksi ACO3:n fosforylaation havaittiin olevan kytköksissä ACO3 proteiinin kertymiseen. Sekä PP2A-B’γ:n että ACO3:n todettiin vaikuttivat vaihtoehtoisen oksidaasin määrään translaation jälkeisellä tasolla, ja sitä kautta solun hapetus-pelkistystasapainoon. Perusaineenvaihdunnan ohella PP2A-B’γ:n havaittiin säätelevän taudinaiheuttajille haitallisen 4-metoksi-indoli-3-yyli-metyyliglukosinolaattin (4MO-I3M glukosinolaatti) muodostusta. Lisäksi PP2A-B’γ vuorovaikutti 4MO-I3M glukosinolaatin muodostusta edesauttavan aktiivisen metyylikierron entsyymien kanssa. PP2A-B’γ:n osoitettiin säätelevän aktiivisen metyylikierron entsyymien muodostamia proteiinikomplekseja ja solun metylaatiokykyä. Tämä tutkimus lisää tietämystämme kasvien sopeutumisesta abioottiseen stressiin sekä ympäristöstressin aikaansaamien aineenvaihdunnan muutosten säätelystä. Yksityiskohtainen tieto kasvin sopeutumis- ja puolustusmekanismeista sekä ympäristöstressin aikaansaamista muutoksista kasvin aineenvaihdunnassa on tärkeää puolustuskykyisempien ja ravinteikkaampien viljelykasvien jalostuksessa.